Pendampingan Pengelolaan Keuangan Dan Pertanggungjawaban Keuangan BUMDes Di Kabupaten Kampar - Rezi Abdurrahman; Yesi Mutia Basri; Al Azhar. A; Edfan Darlis (Asosiasi Dosen Akuntansi Indonesia, 2021)
Law Number 6 of 2014 concerning Villages and Regulation of the Minister of Underdeveloped Villages and Transmigration Number 4 of 2015 encourage villages to independently manage their resources and develop their economies. The implementation of this law is a realization of Village-Owned Enterprises (BUMDes). In managing their finances, many BUMDes managers still don't understand it. How to plan, administer and make financial accountability. This activity aims to provide assistance related to BUMDes financial management. The target audience for this activity is the management of BUMDes Mitra Baru in Taratak Village, Rumbio Jaya District, Kampar Regency. The method of activity is discussion, question and answer and simulation of BUMDes financial report preparation. This activity is expected to improve the performance of BUMDes so that it has an impact on improving the economy of the surrounding community.